Pengaruh Elemen Brand Knowledge dan Brand Equity terhadap Repurchase Intention - Bakti Jean Lawas Lawu (Universitas Kristen Maranatha, 2015)
This study was made to determine the brand knowledge and brand equity effecs towards repurchase intention in Veneta Brands of ink irinter products. The research took place in Bandung. The research was also done using descriptive andcausal analysis. Data were collected through questionnaire method, and were distributed to Veneta consumers that is resided in Bandung city, using nonprobabilty sampling method with judgemental sampling technique. 100 sampleswere used in this research.The result showed that the elements of brand knowledge and brand equity, which is brand loyalty, brand association, perceived quality, and brand image, have a significant effect on repurchase intention variable. The studyalso found that brand awareness and perceived quality are not significantly influence repurchase intention.The implications of this study concluded that increasing the brand loyalty, brand association, and brand image would lead to a better repurchaseintention, by giving more before & after sales services, better quality of service, building a stable and potential relationship with customers through customer relationship management programs, regularly follow up customers needs, and givingspecial promotions to loyal customers..Keywords: brand, brand equity, brand knowledge, repurchase intention